The Reality of Administrative Creativity and its problems of Female Employees at Imam Muhammad bin Saud Islamic University - Al-Harbi, Dalia Abdel Aziz (Journal of Educational and Psychological Sciences, 2019)
The study aimed to identify the degree of practice of administrative creativity and of employees at Imam Muhammad bin Saud Islamic University, and the degree of problems of administrative creativity of employees and recommend propositions that can contribute to the development of administrative creativity of employees at the Female Students Center in Imam Muhammad bin Saud Islamic University. To achieve these goals, the researcher used the descriptive approach; the searcher has used survey questionnaire distributed to a sample of (339) employees. And the study findings were: Agreement among the study sample to practice administrative creativity at an average of (3.47), and agreement among the study sample regarding the existing of obstacles to administrative creativity with an average of (3.70). As for the agreement among the study sample on the proposals that will develop the practice of administrative creativity with an average of (3.62). Based on the study’s findings, the most important recommendation was, simplifying the administrative procedures to the extent that promote independence and flexibility to implement administrative creativity.